Correlations between the prescribing patterns of psychotropic medications and socio-economic factors during the COVID-19 pandemic: A cross-sectional Swedish registry study - Dainty Ei; Gunnar Brådvik; Peter Lindgren; Paul Barach; Tomasz Bochenek (PLoS ONE, 2025)
Background The COVID-19 pandemic has had a profoundly negative impact on all societal sectors, public health systems, and state economies. The pandemic led to high levels of stress, anxiety, depression, insomnia, and substance abuse, while the impact on changes in psychotropic medication prescribing was complex. Despite less restrictive measures in the first stage of the pandemic, Sweden experienced significant mental health consequences and changes in psychotropic medication prescribing. Aim This study aimed to characterize the different psychotropic medication prescribing patterns (antidepressants, anxiolytics, hypnotics and sedatives, and drugs used in addictive disorders: nicotine, alcohol, and opioid dependence) at regional levels and investigate the correlations of disease spread and socio-economic factors with the Swedish regional prescribing patterns during the COVID-19 pandemic. Methods We employed an observational and retrospective design, incorporating time-series analysis, spatial visualization, and regression analysis. Results The prescribing of anxiolytics and drugs used in addictive disorders decreased during the pandemic, with the most striking reductions seen in medications used for nicotine dependence. Considerable regional variations were observed across Sweden during the pandemic years, with antidepressant prescribing increasing slightly, and hypnotics and sedatives showing a relatively stable trend. None of the four key variables of disease spread and socio-economic factors showed a statistically significant correlation with the changes in the prescribing of drugs used for nicotine dependence. Conclusions Our study demonstrated differentiated changes in psychotropic medication prescribing patterns during the COVID-19 pandemic in Sweden. We found a pandemic effect on nicotine dependence drug prescribing, which the key variables could not explain. Targeted mental health interventions and specific regional health policies should be developed to reduce disparities and address regional variations during future health emergencies.